Rikki - Genechten, Guido van.; Allahverdiyeva, Farida (İstanbul : Hep Kitap, 2023)
A bunny named Ricky shows bravery when he chooses to sleep outside in his tent with his Zorro cape to cool off on a hot night.
K-3.
Turkish.
Keywords: Picture Books. -- Juvenile fiction; Courage -- Fiction; Rabbits -- Fiction; Picture books for children